Enzymatically modified LDL promotes foam cell formation in smooth muscle cells via macropinocytosis and enhances receptor mediated uptake of oxidized LDL - Chellan, Bijoy (Arterioscler Thromb Vasc Biol, 2016)
OBJECTIVE: Enzyme-modified LDL (ELDL) is present in human atherosclerotic lesions. Our objective is to understand the mechanisms of ELDL uptake and its effects on vascular smooth muscle cells. APPROACH AND RESULTS: Transformation of murine aortic SMC into foam cells in response to ELDL was analyzed. ELDL, but not acetylated or oxidized LDL, was very potent in inducing SMC foam cell formation. Inhibitors of macropinocytosis (LY294002, wortmannin, amiloride) attenuated ELDL uptake. In contrast, inhibitors of receptor mediated endocytosis (dynasore, sucrose) and inhibitor of caveolae/lipid raft mediated endocytosis (filipin) had no effect on ELDL uptake in SMC, suggesting that macropinocytosis is the main mechanism of ELDL uptake by SMC. Receptor for advanced glycation end products (RAGE) is not obligatory for ELDL induced SMC foam cell formation, but primes SMC for the uptake of oxidized LDL in a RAGE-dependent manner. ELDL increased intracellular reactive oxygen species (ROS), cytosolic calcium, and expression of lectin like oxidized LDL receptor (LOX-1) in wild type SMC but not in RAGE(−/−) SMC. The macropinocytotic uptake of ELDL is regulated predominantly by intracellular calcium since ELDL uptake was completely inhibited by pretreatment with the calcium channel inhibitor lacidipine in wild type and RAGE(−/−) SMC. This is in contrast to pretreatment with PI3K inhibitors which completely prevented ELDL uptake in RAGE(−/−) SMC, but only partially in wild type SMC. CONCLUSIONS: ELDL is highly potent in inducing foam cells in murine SMC. ELDL endocytosis is mediated by calcium dependent macropinocytosis. Priming SMC with ELDL enhances the uptake of oxidized LDL.